Computed tomography analysis of impact response of lightweight sandwich panels with micro lattice core. (April 2018) - Abrate, S; Epasto, G; Kara, E; Crupi, V; Guglielmino, E; Aykul, H
One of the main focuses in transportation engineering is the application of sandwich materials in order to create safer and efficient vehicles. The main focus of this study was the application of 3D computed tomography for analyzing the responses of sandwich panels with micro lattice core subjected to impact loading. Micro lattice specimens were manufactured using Ti-6Al-4V powder by means of a direct metal laser sintering system. A theoretical model was applied for predicting the failure initiation loads under impact loading. The predictions presented good consistency with the experimental measurements. The 3D computed tomography system was used for the analysis of the collapse modes of the micro lattice sandwich panels after low-velocity impact tests. Experimental and theoretical results proved that lightweight sandwich panels with micro lattice cores are excellent energy absorbers and, therefore, they could have significant applications in the transportation industry.